GENETIC DIVERSITY OF VIR COLLECTIONS OF THE RAPHANUS SATIVUS L. (SMALL RADISH AND RADISH) - A. B. Kurina (Ovoŝi Rossii, 2018)
The study on the diversity of root plants in the species of Raphanus sativus L., which are available in the collection of VIR, enables to comprehensively evaluate the collection of small radish and radish, making descriptions of new forms and cultivar-types, and revealing the biological features of the formation of photosynthetic apparatus, yielding abilities, resistance to biotic and abiotic stressors. This article is the first part of a series of articles devoted to the study of the gene pool of root plants of the species R. sativus L. from the VIR collection. The experimental part of the article includes the results of a study of previously unexplored accessions from the radish collection, the following articles will be devoted to the radish gene pool. As a result of the research conducted in 2016-2017. 110 samples of radish of different eco-geographical origin and representing variety of cultivar type were studied. The studied radish samples were combined into several groups according to the duration of the growing season (early ripening, mid-ripening and late ripening). A longer vegetation period in radish in winter-time-growing was observed in case of insufficient illumination, but some accesions of the red oval-rounded cultivar type (k-2133, k-2343, k-1742, k-2404) have not shown any change in vegetation period. There was a strong change in the shape of the root crop when growing in winter under insufficient illumination. Samples that are capable to form a consumed organ in such conditions without changing the shape of the root crop and vegetation period were k-2404, Netherlands, k-2133, Tanzania, k-2185, Poland, k-2343, Iceland, k-1666, Russia. Among the accessions of the red-oval-round cultivar type, varieties from the Netherlands, the Czech Republic and Poland emerged, formed a short-rooted, compact rosette with an elevated leaf arrangement in all growing conditions. The formation of high productivity in the open field types was revealed in most cultivars, only the samples of the cultivars White long and Red gave high yields in protected soil. In the spring greenhouse a higher quality yield was obtained. Seven samples of radish have been selected, which are valuable for nearest breeding pro-gram. They can be used as a source breeding material for productivity, root quality, resistance to bolting at low temperatures and a long day.